Beyond MELD Predictors of Post TIPSS Acute Liver Failure the Lesson Learned - Verma, Ritu; Jain, Nishchint; Arora, Abhishek; Gamangatti, Shivanand; Chaturvedi, Shailendra (Indian Journal of Radiology and Imaging, 2021)
TIPSS is safe and effective procedure for relieving portal hypertension by creating a low resistance portosystemic shunt. TIPSS reduces portal perfusion by 80 to 100% which then gradually gets partially compensated by increased flow from hepatic artery. Post TIPSS liver function shows brief deterioration which tends to start recovering in few weeks. However, progressive liver failure requiring emergency transplant or death remains a serious concern after TIPSS creation. The causes of post TIPSS liver failure are diverse and difficult to predict. Due to its rarity the definition of post TIPSS liver decompensation is also not well described in literature. Till date MELDNa score has been considered as the most reliable predictor of post TIPSS liver decompensation. In common practice post TIPSS liver failure is less likely in patients with model for end-stage liver disease (MELD) score less than 18. We have experienced two unusual cases of post-TIPSS liver failure (PTLF) in patients with initial acceptable/low MELD score and the importance of non-MELD factors that may negatively influence post TIPSS outcome. Most of these can be routinely investigated prior to creating shunt thereby identifying patients at high risk of developing PTLF.
Keywords: acute liver failure; hepatic encephalopathy; PTLF; TIPSS